2013
DOI: 10.1016/j.jpain.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Anomalies and Chronic Pain: A Quantitative Meta-Analysis of Gray Matter Volume

Abstract: The diversity of chronic pain syndromes and the methods employed to study them make integrating experimental findings challenging. This study performed coordinate-based meta-analyses using voxel-based morphometry imaging results to examine gray matter volume (GMV) differences between chronic pain patients and healthy controls. There were 12 clusters where GMV was decreased in patients compared with controls, including many regions thought to be part of the “pain matrix” of regions involved in pain perception, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
225
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(242 citation statements)
references
References 104 publications
(131 reference statements)
13
225
2
2
Order By: Relevance
“…If acute pain does not affect the hedonic experience of rewards (Gandhi et al, 2013), reduced reward responsiveness in PCPs could be a consequence of the long-term effects of pain or a marker of chronic pain vulnerability (Denk et al, 2014). The trend towards reduction in nucleus accumbens volume concurs with a previous study that showed reduction in its size as pain became chronic and in a meta-analyses of morphometric studies on PCPs (Baliki et al, 2012;Smallwood et al, 2013). However, one study on rheumatoid arthritis patients found increased nucleus accumbens volume (Wartolowska et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…If acute pain does not affect the hedonic experience of rewards (Gandhi et al, 2013), reduced reward responsiveness in PCPs could be a consequence of the long-term effects of pain or a marker of chronic pain vulnerability (Denk et al, 2014). The trend towards reduction in nucleus accumbens volume concurs with a previous study that showed reduction in its size as pain became chronic and in a meta-analyses of morphometric studies on PCPs (Baliki et al, 2012;Smallwood et al, 2013). However, one study on rheumatoid arthritis patients found increased nucleus accumbens volume (Wartolowska et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Ventral striatum grey matter density has been shown to correlate with both a combination score of personality traits that included reward drive and reward responsiveness and degree of placebo analgesia in healthy controls (Schweinhardt et al, 2009). Furthermore, a systematic meta-analysis of brain structure in PCP demonstrated reduced volume in the area of the nucleus accumbens (Smallwood et al, 2013), and nucleus accumbens grey matter density has been shown to decrease after the onset of chronic back pain (Baliki et al, 2012). The biological mechanisms underlying the observed volume change are unknown, but chronic pain induced changes in several neurotransmitter systems (D'Angio et al, 1987;Li et al, 2001;Chang et al, 2014;Schwartz et al, 2014), and connectivity with other basal ganglia as well as cortical regions (Mansour et al, 2013;Chang et al, 2014) may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that examined structural brain alterations in chronic pain focused on a variety of pain phenotypes, such as migraine, back pain, osteoarthritis, and fibromyalgia. [6][7][8][9][10][11][12][13][14][15] Typically, the study size was small; the largest studies included approximately 100 subjects. The small sample sizes of these studies led to a modest statistical power, thereby influencing the reproducibility of the results.…”
mentioning
confidence: 99%
“…The insula is a functionally heterogeneous brain region that participates in pain perception, emotional processing and interoception. It was commonly revealed that there was a difference in gray matter volume in chronic pain patients compared with healthy controls [47]. The insular networks were found to be altered by migraine headache [54,55], and our research team demonstrated that migraine patients have dysfunctional connectivity involved with the insula [8,39].…”
Section: The Potential Mechanism Of Active Acupuncture Therapy For MImentioning
confidence: 73%
“…Based on our results, we detected that a long course of acupuncture treatment on active acupoints affected the hippocampus, which is associated with cognitive components of pain processing, as well as a major component of the human brain that links affective states with memory processing. The hippocampus was described as having increased gray matter volume in patients suffering chronic pain in a meta-analysis [47], and this was confirmed in a recent migraine study [6]. It seems to frequently participate in the central effects of acupuncture.…”
Section: The Difference In Resting-state Brain Activity Evoked By Actmentioning
confidence: 83%